Some Focusing Points in Development of Modern Modeling and Simulation Technology - Li, Bo Hu (Systems Modeling and Simulation: Theory and Applications, 2005)
Today, M&S combined with High Performance Computing is becoming the third important means for recognizing and rebuilding the objective world besides the theory research and experiment research. At present, the tendency of system modeling and simulation technology is developing towards networkitization, virtualization, intelligentization, collaboratization and pervasivization. Based on the research fruits of paper1 and author’s recent research projects, this paper further discusses the meanings of modern M&S and its architecture. Furthermore, some focusing points in recent research and application of M&S are also discussed and prospected, including networkitized M&S technology based on modern network techniques, M&S technology on synthetized nature environment, Intelligent system modeling and intelligent simulation system, M&S technology of complex system and open, complex, huge system, virtual prototyping engineering technology, high performance computer, pervasive simulation technology etc.. At last, some conclusions are given.